Toxic Remedies: On the Cultivation of Medicinal Plants and Urban Ecologies. Issue 2 (3rd April 2021) - Mohácsi, Gergely
Abstract: Growing concerns with air-pollution, contaminated drinking water, and deteriorated sewerage infrastructures contributed to an increasing environmental awareness in Vietnam during the past decade. At urban sites, such as herbal gardens in Hanoi, these ecological concerns converge with medicinal itineraries of East Asian herbal medications and the health of a rising middle-class. In these emerging chemosocial configurations, public health becomes an environmental issue, and the city holds out the promise of a resilient space of planetary health. To illustrate such lateral movements, this article focuses on the cultivation and transplantation of medicinal plants in central Hanoi. Thinking through the question of how people and herbs come to cultivate and be cultivated by one another, I argue, helps to understand the public health stakes of chemosocial infrastructures in a rapidly urbanizing Vietnam and, more generally, in urban transformations throughout Asia. At stake both in the transformation of plants into pharmaceutical products and in the modes of transplanting knowledges and methods from one world (or discipline) to another is the lateral mobility between East Asian medical practices and STS methodologies.